Respuesta :

Answer:

x = 1

y= -2

Step-by-step explanation:

to solve this system of equation , simultaneously using the substitution method

we say let

7 x + y = 5 ............................................. equation 1

2x - y = 4 ................................................... equation 2

from equation 2

2x - y = 4 ................................................... equation 2

2x - 4 = y

y = 2x -4.......................................................... equation 3

put the value of the y = 2x -4 into equation 1

7 x + y = 5 ............................................. equation 1

7x + 2x - 4 = 5

9x-4 = 5

9x = 5 + 4

9x = 9

divide both sides by the coefficient of x which is 9

9x/9 = 9/9

x = 1

substitute the value of x = 1 into equation 3

y = 2x -4.......................................................... equation 3

y = 2(1) -4

y = 2 - 4

y = -2

to check if you are correct put the value of x and y into any of the equations and you will see that the left hand side will be equal to the right hand side.

2x - y = 4 ................................................... equation 2

2(1) -(-2) = 4

2 + 2 = 4

4=4................................... proved

ACCESS MORE